Nutrition, aging and cancer: lessons from dietary intervention studies. Issue 1 (December 2016) - Carruba, Giuseppe; Cocciadiferro, Letizia; Di Cristina, Antonietta; Granata, Orazia; Dolcemascolo, Cecilia; Campisi, Ildegarda; Zarcone, Maurizio; Cinquegrani, Maria; Traina, Adele
Abstract There is convincing epidemiological and clinical evidence that, independent of aging, lifestyle and, notably, nutrition are associated with development or progression of major human cancers, including breast, prostate, colorectal tumors, and an increasingly large collection of diet-related cancers. Mechanisms underlying this association are mostly related to the distinct epigenetic effects of different dietary patterns. In this context, Mediterranean diet has been reported to significantly reduce mortality rates for various chronic illnesses, including cardiovascular diseases, neurodegenerative diseases and cancer. Although many observational studies have supported this evidence, dietary intervention studies using a Mediterranean dietary pattern or its selected food components are still limited and affected by a rather large variability in characteristics of study subjects, type and length of intervention, selected end-points and statistical analysis. Here we review data of two of our intervention studies, the MeDiet study and the DiMeSa project, aimed at assessing the effects of traditional Mediterranean diet and/or its component(s) on a large panel of both plasma and urine biomarkers. Both published and unpublished results are presented and discussed.